2000
DOI: 10.1054/bjoc.1999.0912
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and academic outcome following cranial irradiation and chemotherapy in children: a longitudinal study

Abstract: Cranial irradiation therapy (CRT) and chemotherapy are associated with neurobehavioural deficits. Many studies have investigated late effects of these treatments, but few have evaluated changes in abilities over time. This study employed a longitudinal design to map abilities following these treatments. Three groups of children were studied: Group 1 (n = 35): children treated with CRT (18 Gy) + chemotherapy, aged 5 years or less at time of diagnosis; Group 2 (n = 19): children treated with chemotherapy alone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(99 citation statements)
references
References 39 publications
4
92
1
2
Order By: Relevance
“…CRT is associated with poor educational outcomes among survivors of childhood cancer, 24,27,28 as we also demonstrated in the current study. Reports have indicated that IT MTX is a risk factor for poor cognitive performance and neurologic function.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CRT is associated with poor educational outcomes among survivors of childhood cancer, 24,27,28 as we also demonstrated in the current study. Reports have indicated that IT MTX is a risk factor for poor cognitive performance and neurologic function.…”
Section: Discussionsupporting
confidence: 85%
“…Younger age at diagnosis and/or treatment 7,14,[24][25][26] ; cranial or craniospinal radiotherapy (CRT) and/or intrathecal methotrexate (IT MTX) 15,24,25,[27][28][29] ; higher therapeutic doses of CRT or IT MTX 17,24 ; and diagnoses of central nervous system (CNS) tumors, leukemia (particularly acute lymphoblastic leukemia [ALL]), Hodgkin lymphoma, or neuroblastoma 13,15,30 as well as being female, [30][31][32][33] of lower socioeconomic status (SES), 20 and having a longer time since diagnosis 24 have been reported to be associated with an increased risk of poorer educational outcomes. Previous studies have not always assessed the potential confounding effects of missed school, 34 SES, 35 and physical health or physical impairments.…”
mentioning
confidence: 99%
“…This has resulted in an increasing interest in the late effects of disease and treatment on physical, mental and social well-being of the survivors. Several elements of therapy for ALL may affect the function of the central and peripheral nervous system, and cognitive deficits (e.g., Anderson et al, 2000;Brown et al, 1992;Butler et al, 1994;Moleski, 2000;Ochs et al, 1991) as well as gross and fine motor impairments (Galea et al, 2004;HarilaSaari et al, 2001;Lehtinen et al, 2002;Reinders-Messelink et al, 1996;Vainionpaa, 1993;Wright et al, 1998) have been reported in survivors of childhood ALL. CNS-directed treatment is a standard component of therapy for ALL.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of cognitive decline associated with irradiation for brain tumors and prophylaxis for leukemia has received much attention in children but less so in adults (1)(2)(3). N evertheless, the problem of cognitive impairment associated with cranial irradiation is well recognized in adults (4 -6).…”
mentioning
confidence: 99%